Persepsi Wisatawan Terhadap Objek Wisata Air Terjun Lamesau Sebagai Tujuan Wisata - Ilma Yamti; La Ode Amaluddin; La Harudu (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Lameseu Waterfall is a waterfall located in Lametono Village, Lasolo District, North Konawe Regency. This waterfall has a pool of water right under the waterfall and visitors can enjoy its coolness because it is still formed naturally. The purpose of this study is to describe the perceptions of tourists towards the object of the Lamseseu waterfall tourist area. This study used descriptive qualitative method. Data was collected through questionnaires, interviews and documentation. The results showed an average score of 4.36, this means that the community strongly agrees that the object of the Lameseu waterfall tourist area in Lametono Village, Lasolo District has a very beautiful attraction so that it can attract tourists to visit.